The corepressor activity of Alien is controlled by CREB‐binding protein/p300. (18th March 2013) - Eckey, Maren; Kraft, Florian; Kob, Robert; Escher, Niko; Asim, Mohammad; Fischer, Heike; Fritsche, Marie K.; Melle, Christian; Baniahmad, Aria
Abstract : The regulation of gene repression by corepressors is a controlled process. Surface‐enhanced laser desorption ionization MS proteomic analysis and a yeast two‐hybrid screen showed independently that the corepressor Alien interacts with the CREB‐binding protein (CBP) coactivator. This interaction was further confirmed by coimmunoprecipitation and glutathione S ‐transferase pull‐down experiments, suggesting that Alien interacts in vivo and in vitro with the histone acetyltransferase (HAT) coactivators CBP and its paralog p300. Acetylation detection experiments indicated that Alien is acetylated in vivo . Furthermore, Alien interacts with the central region of CBP/p300 containing the HAT domain and becomes acetylated in vitro . When an inhibitor of CBP/p300 HAT activity was employed, the Alien‐mediated silencing was enhanced. Thus, these findings suggest crosstalk between corepressors and coactivators, and indicate fine‐tuning of corepressor function by post‐translational modification through corepressor acetylation. Structured digital abstract: p300 binds to Alien α by pull down (View interaction) Alien α physically interacts with CBP by two hybrid (View interaction) Alien α physically interacts with MLK2 by two hybrid (View interaction) p300 acetylates Alien α by acetylation assay (View interaction) Alien α physically interacts with NAP1 by two hybrid (View interaction) Alien α physically interacts with TAFI68 by two hybrid (View interaction) Alien α physically interacts with CBP by anti bait coimmunoprecipitation (View Interaction: 1, 2, 3) Alien α binds to CBP by pull down (View interaction) Abstract : Gene silencing by transcriptional repressors is mediated in part by corepressors. Here, we show that the corepressor Alien binds in vivo and in vitro to the coactivator CBP/p300. The interaction with these histone acetyltransferases leads to acetylation of Alien and functionally to reduced Alien‐mediated transcriptional silencing. The data indicate how silencing function is modulated by post‐translational modification.